N-Methyl-D-Aspartate Receptor Hypofunction in Meg-01 Cells Reveals a Role for Intracellular Calcium Homeostasis in Balancing Megakaryocytic-Erythroid Differentiation - Hearn JI; Green TN; Chopra M; Nursalim YNS; Ladvanszky L; Knowlton N; Blenkiron C; Poulsen RC; Singleton DC; Bohlander SK; Kalev-Zylinska ML (Thieme Gruppe, 2020)
The release of calcium ions (Ca2+) from the endoplasmic reticulum (ER) and related store-operated calcium entry (SOCE) regulate maturation of normal megakaryocytes. The N-methyl-D-aspartate (NMDA) receptor (NMDAR) provides an additional mechanism for Ca2+ influx in megakaryocytic cells, but its role remains unclear. We created a model of NMDAR hypofunction in Meg-01 cells using CRISPR-Cas9 mediated knockout of the GRIN1 gene, which encodes an obligate, GluN1 subunit of the NMDAR. We found that compared with unmodified Meg-01 cells, Meg-01-GRIN1 -/- cells underwent atypical differentiation biased toward erythropoiesis, associated with increased basal ER stress and cell death. Resting cytoplasmic Ca2+ levels were higher in Meg-01-GRIN1 -/- cells, but ER Ca2+ release and SOCE were lower after activation. Lysosome-related organelles accumulated including immature dense granules that may have contributed an alternative source of intracellular Ca2+. Microarray analysis revealed that Meg-01-GRIN1 -/- cells had deregulated expression of transcripts involved in Ca2+ metabolism, together with a shift in the pattern of hematopoietic transcription factors toward erythropoiesis. In keeping with the observed pro-cell death phenotype induced by GRIN1 deletion, memantine (NMDAR inhibitor) increased cytotoxic effects of cytarabine in unmodified Meg-01 cells. In conclusion, NMDARs comprise an integral component of the Ca2+ regulatory network in Meg-01 cells that help balance ER stress and megakaryocytic-erythroid differentiation. We also provide the first evidence that megakaryocytic NMDARs regulate biogenesis of lysosome-related organelles, including dense granules. Our results argue that intracellular Ca2+ homeostasis may be more important for normal megakaryocytic and erythroid differentiation than currently recognized; thus, modulation may offer therapeutic opportunities.
Keywords: Apoptosis; CRISPR-Cas Systems; Calcium; Calcium Signaling; Carcinogenesis; Cell Differentiation; Cell Line, Tumor; Endoplasmic Reticulum Stress; Erythrocytes; Homeostasis; Humans; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Megakaryocytes; Receptors, N-Methyl-D-Aspartate; Thrombopoiesis